2017
DOI: 10.1017/s1463423617000822
|View full text |Cite|
|
Sign up to set email alerts
|

Why do patients with minor complaints choose emergency departments and does satisfaction with primary care services influence their decisions?

Abstract: The frequency of admission to EDs as a first contact of care was extremely high in the absence of a referral system. Patients who did not have family doctors in the settlement where they live put an extra burden on the EDs. Overall, patient satisfaction with their GPs did not influence the number of visits to EDs but accessibility remains a big challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…18 Similar findings were reported in Turkey and Iran. 13,16 This study reported that organizational barriers were the most common barriers toward visiting PHCs. Organizational barriers included cleanliness, lack of preventive services and difficulty in obtaining referrals.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…18 Similar findings were reported in Turkey and Iran. 13,16 This study reported that organizational barriers were the most common barriers toward visiting PHCs. Organizational barriers included cleanliness, lack of preventive services and difficulty in obtaining referrals.…”
Section: Discussionmentioning
confidence: 92%
“… 1 In Turkey, the mean patients’ satisfaction with family physician offices was reported to be 68.1%. 13 In Lebanon, it was reported that 60.23% and 36.43% of patients were satisfied and very satisfied, respectively, with the services provided in PHCs. 14 Different study settings and methodologies could explain the differences between the findings from the current study and other international and Saudi studies which revealed that patients’ satisfaction with PHCs was ranging from 75% and above.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Emergency departments receive more visits than any other clinical branches do in our country (Turkiye). [ 1 ] The leading causes may include expectation for faster health service access, immediate treatment in emergency room, faster access to laboratory and radiological examinations, and access to a variety of specialists other than those of emergency medicine. [ 2 , 3 ] However, this may also bring excessive burden for diagnostic and therapeutic workforce.…”
Section: Introductionmentioning
confidence: 99%
“…In the article by Akpinar et al (2017), the name of a hospital was mistakenly listed as “XXXXX” in the abstract. The authors and the publishers would like to apologies for this mistake.…”
mentioning
confidence: 99%